Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.5204/ssj.1847
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Student Experience During the Pandemic and Beyond

Abstract: This article reports the findings from a small-scale, qualitative and phenomenological institutional research project, undertaken during the COVID-19 pandemic, on the experiences of undergraduate students from groups who are traditionally under-represented in higher education in the United Kingdom.  Documenting the first two phases of a longitudinal study carried out at one university in England, the over-arching research question investigated here using semi-structured interviews was: How has the ongoing COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…While quarantine, social distancing, and border restrictions are health measures for COVID-19 containment, our study indicates these strategies increase instances of social and physical isolation, and the amount of time spent away from friends and families (Lewnard & Lo, 2020). Feelings of exclusion, disconnection, loneliness, and isolation among international students (Sullivan & Kashubeck-West, 2015) have detrimental effects on their mental health and wellbeing, and during crises, especially COVID-19, this can worsen (Brooks et al, 2020;Sanderson et al, 2021). In our study, loneliness was one key experience.…”
Section: Isolation and Lonelinessmentioning
confidence: 54%
See 2 more Smart Citations
“…While quarantine, social distancing, and border restrictions are health measures for COVID-19 containment, our study indicates these strategies increase instances of social and physical isolation, and the amount of time spent away from friends and families (Lewnard & Lo, 2020). Feelings of exclusion, disconnection, loneliness, and isolation among international students (Sullivan & Kashubeck-West, 2015) have detrimental effects on their mental health and wellbeing, and during crises, especially COVID-19, this can worsen (Brooks et al, 2020;Sanderson et al, 2021). In our study, loneliness was one key experience.…”
Section: Isolation and Lonelinessmentioning
confidence: 54%
“…The identified experiences also necessitate universities to reconsider how they support and engage international students, as this can help ameliorate the pandemic's effects on their wellbeing and academic life. As Sanderson et al (2021) found in their study on supporting student experience during the pandemic and beyond, such effective support services can improve students' mental, social and psychological wellbeing. We propose that such support practices should entail universities adopting a more human-centred, inclusive, equitable and sustainable approach, regardless of student backgrounds.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Students often find it harder to connect with peers where there is an online or blended delivery of subject content. The divide is greater for students from non-traditional backgrounds who are less likely to have access to key study resources and an appropriate workspace at home (Sanderson et al, 2021). This is compounded by the individual experiences of students throughout the COVID-19 pandemic such as changes to work and caring responsibilities.…”
Section: Introductionmentioning
confidence: 99%